How perceived supervisor support effects workplace deviance? Mediating role of perceived organizational support - Saira Iqbal Khan; Atif Mahmood; Sara Kanwal; Yasir Latif (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
Employee-organization relationship has become a topic of prime concern for many firms across world, particularly in developing nations. However, little is known about its predictors in banking industry. Moreover, there is scarcity of literature regarding the underlying mediating mechanisms. Thus, purpose of this study is to investigate the mediating role of perceived organizational support on relationship between perceived supervisor support and workplace deviance within a non-western context. After preliminary pilot testing, via convenience sampling technique, survey questionnaires were distributed among 800 front-line employees working in the top banks of Pakistan, and 614 completely filled instruments were received back. SEM results verify that perceived organizational support partially mediates the impact of supervisor support and workplace deviance, implying that employees perceive more support when their organizations offer commensurate rewards, opportunities for growth and participation in decision making. This study is imperative for policy making in order to overcome counter-productive behaviors among front-line employees in both public and private banks of Pakistan. However, outcomes of this research are limited to the Pakistani context.
Keywords: 330; perceived organizational support; perceived supervisor support; workplace deviance; and organizational support theory